Boomtowns: Local shocks and inequality in 1920s California - Sarah Quincy; Rowena Gray (European Historical Economics Society (EHES), 2022)
The 1920s in the United States were a time of high income and wealth growth and rising inequality, up to the peak in 1929. It was an era of technological innovations such as electrification as well as booms in consumer durables, housing, and asset markets. The degree to which these skill-biased opportunities shaped property wealth inequality depends on how local and macro-level industrial shocks were capitalized into real estate values. We uncover the pattern for California, a state where shocks in oil, housing and stocks were large, and which has annual data on city-level property values and population counts. We show that electricity both increased values and reduced inequality in property values, while other booms had more short-lived and localized effects.
Keywords: N12; N33; N92; R31; 330; wealth inequality; booms; Roaring 20s